PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ORGANISASI KEMAHASISWAAN MENGGUNAKAN METODE SIMULASI MONTE CARLO DI UIN SJECJ M. DJAMIL DJAMBEK BUKITTINGGI - Maharani, Devina; Efriyanti, Liza; Supriadi, Supriadi; Zakir, Supratman (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to design a Decision Support System (DSS) for selecting student organizations at UIN Sjech M. Djamil Djambek Bukittinggi. The background of this study stems from the lack of objective information and the mismatch between students’ interests and the types of organizations available, which often leads to inappropriate organizational choices. To address this issue, the study seeks to design a model that assists students in choosing student organizations that align with their preferences and personal characteristics using the Monte Carlo simulation method.The Monte Carlo simulation method is employed to predict the number of prospective members for each student organization by generating random numbers based on historical data from 2022 to 2024. The simulation process was conducted over 365 iterations for each organization, applying a random distribution approach to produce realistic and representative outcomes. The simulation results were then validated using the Mean Absolute Error (MAE) method to measure the model’s accuracy against actual 2024 data. The validation results showed an MAE value of 22.25 and a model accuracy of 79.63%. These findings indicate that the developed simulation model is sufficiently accurate and reliable in predicting student interest in various organizations. Furthermore, the system successfully identified the top five most popular student organizations based on the highest predicted number of members, which can serve as a reference for the university in developing organizational guidance and promotional strategies. Overall, this system provides a tangible contribution to supporting more objective and data-driven decision-making processes within the higher education environment, particularly in the field of student affairs.